Analisis Kebijakan Permendikbud Nomor 30 Tahun 2017 (Tentang Peran Keluarga dan Masyarakat Terhadap Pendidikan Anak) - Desi Karmila; Yaswinda Yaswinda (Jurnal Family Education, 2022)
The implementation of education requires solid cooperation between the family, the environment and the education unit. Article 2 of the Minister of Education and Culture Number 30 of 2017 means that the contribution of the family in the provision of education is intended to: (1) increase the awareness and responsibility between educational units, families and regions towards the implementation of education, (2) empower children's personality education (3) increase family awareness towards children's education (4) building energy of cooperation between educational units, families, and the environment, and (5) providing a safe, comfortable and enjoyable environment in the learning process. This research belongs to the type of descriptive qualitative research with observation methods equipped with previous literature studies. Respondents were 2 principals from each kindergarten and 2 teaching teachers from each kindergarten. This study will examine how the implementation of Permendikbud Number 30 of 2017 on children's education in schools.From the results of interviews conducted in each kindergarten on April 4, 2022, namely. The results of interviews at the Amanah Kindergarten institution explained that parents and the community in the surrounding environment had participated in being involved in the education of their children and vice versa in the Pertiwi III Ladang Panjang kindergarten institution that parents and the community had also been involved in children's education. The results of the study describe the school's efforts in implementing Permendikbud Number 20 of 2917, namely involving parents directly in various school activities, parenting programs are also needed for parents of children. The school includes parents in every school agenda. . this is very much in line with the strategy of the Minister of Education and Culture Number 30 of 2017 as a reference base for families, the environment and schools in supporting children's education from an early age.